Professional Responsibility in Practice: Advocacy in the Law School Curriculum - Judith Dickson; Susan Campbell (Legal Education Review)
The marginalisation of the teaching and learning of legal research in the Australian law school curriculum is, in the author’s experience, a condition common to many law schools. This is reflected in the reluctance of some law teachers to include legal research skills in the substantive law teaching schedule — often the result of unwillingness on the part of law school administrators to provide the resources necessary to ensure that such integration does not place a disproportionately heavy burden of assessment on those who are tempted. However, this may only be one of many reasons for the marginalisation of legal research in the law school experience. Rather than analyse the reasons for this marginalisation, this article deals with what needs to be done to rectify the situation, and to ensure that the teaching of legal research can be integrated into the law school curriculum in a meaningful way. This requires the use of teaching and learning theory which focuses on student-centred learning. The adoption of legal research as an integral part of the Australian law school curriculum is outlined through the use of a normative model. This objective is predicated on the assumption that legal research is an essential skill for lawyers and law students alike, and therefore should be afforded more weight in the law school curriculum. The integration of legal research, not only into the objectives of law schools but also into the fabric of the teaching and learning program, is a fundamental requirement for the production of a superior law graduate.